Copper Nanoparticles Differentially Target Testis of the Catfish, Clarias batrachus: In vivo and In vitro Study - Murugananthkumar, Raju; Rajesh, Desapogu; Senthilkumaran, Balasubramanian (Frontiers in Environmental Science, 2016)
Present study examined the impact of copper (Cu) as nanoparticle (Cu-NPs) and soluble form (CuSO4) in adult male catfish Clarias batrachus. Following treatment, upregulation of transcripts of several testis-related genes and increased androgen levels were evident. Though profound promotional effect was seen at gene and androgen levels, structural analysis revealed completely different scenario. Histological observations of testis showed disruption of basal lamina, distinct spermatogonium and enlarged spermatocytes in the treated groups. Quite alarmingly, transmission electron microscopic analysis showed damage of testicular lumen with irregular basal lamina and distinctive spermatocytes. In addition, Sertoli cells and erythrocytes exhibited damage after Cu treatments. Cytotoxic effects of Cu in catfish primary testis and TM3 Leydig cells showed cytotoxicity which is correlated well with morphological and flow cytometric analysis. Taken together, the results demonstrated that low dose of Cu/Cu-NPs can be detrimental to catfish testicular recrudescence vis-à-vis reproduction and the toxic effect manifest drastically in in vitro cultures.